Pengaruh Keharmonisan Keluarga terhadap Self Esteem Siswa - Khusnul, Maqfiroh; Dini, Rakhmawati; Windaniati, Windaniati (Jurnal Wahana Konseling, 2024)
This research aims to determine the influence of family harmony on self-esteem among students at SMK Negeri 7 Semarang. The population in this study was 612 with a sample of 37 students. This research uses a quantitative approach with a simple linear regression analysis method with the help of SPSS 25 to process the data. The data collection tools used in this research are the family harmony scale and the self-esteem scale, both of these scales use a Likert scale. The results of this research state that family harmony has an influence on self-esteem, where the higher the family harmony, the higher the self-esteem or self-esteem that students have for themselves. This can be seen from the output results of the hypothesis test that the calculated F value is 123,636 with a significance level of 0.000 < 0.05, and the correlation value (R) is 0.883, from the output data we obtain a coefficient of determination (R Square) of 0.779, which means that the influence of the independent variable (family harmony) on the dependent variable (self esteem) is 77.9%.